The Internet of Things and Agriculture: Role and Advantages in Malaysia - Ismail, Ahmad Perbuana; Salleh, Nurul Azita (CENTRAL ASIA AND THE CAUCASUS, 2024)
The implementation of Agriculture 4.0 has created a new word to identify those players using this new and much more sophisticated model: the Agri-tech industry. In spite of the misunderstanding that people may have about the agricultural climate, the Internet of Things ( IoT) is a extremely creative technology that offers many inventive avenues to modernize the agricultural sector and produce greater opportunities, the reality is that today's agricultural industry is more data-centric, efficient, and intelligent than ever before. Almost every sector has been redesigned by the exponential growth of Internet of Things (IoT) based technologies, including smart agriculture, which has moved the sector from statistical to quantitative approaches. These groundbreaking developments are shaking up traditional farming practices and generating new prospects along with a variety of challenges. The literature reviewed focused on The Internet of Things (IOT) in the field of agriculture and identified current and future IoT trends in agriculture and highlighted the role and advantages of farmers' organizations in ensuring sustainable food supply and helping farmers increase their incomes. The use of IoT in fields, orchards, and management would also enable farmers to reap the benefits of a wide range of technology.